MIXED LIGAND COMPLEXES OF NICKEL(II), COPPER(II) AND ZINC(II) WITH NICOTINANILIDE AND THIOCYANATE: Life Science-Organic Chemistry - KULANDAI RAJA BALAN, A. MARIA; NICHOLAS ASHOK, R. FRANCIS; M. VASANTHI; R. PRABU; A. PAULRAJ (International Journal of Life Science and Pharma Research, 2013)
Mixed ligand nickel(II), copper(II) and zinc(II) complexes of nicotinanilide and thiocyanate were prepared. Metal complexes were characterized by molar conductivity measurements, micro elemental analysis, FT-IR, UV-Visible spectroscopy, electrochemical and antimicrobial studies. The complexes are of 1: 2 (metal : ligand) stoichiometry and are non-electrolytes in solution. The structural analysis indicates a four-coordinated MN2S2 chromophore in a distorted tetrahedral geometry by two nicotinanilide and two thiocyanate ligands.